Primary percutaneous coronary intervention is appropriate in transient ST-elevation myocardial infarction - Lumir Koc (Biomedical Papers, 2022)
Introduction. Reperfusion therapy by primary percutaneous coronary intervention (PPCI) is generally indicated in patients suffering from acute myocardial infarction (MI) with ST-segment elevation (STEMI). Prior to hospital admission, full ST-segment resolution (fSTR) may occur. Optimal management of such patients with transient STEMI (TSTEMI) is potentially challenging. Our aim was to evaluate the hypothesis that in TSTEMI patients, patency of infarct related artery (IRA) is achieved before PPCI, and to compare the outcome of TSTEMI and STEMI patients during a prolonged follow-up. Material and Methods. Three hundred consecutive adult STEMI patients were referred to catheterization laboratory. In all patients, standard 12 lead ECGs were obtained both at the time of the first medical contact, and on catheterization laboratory admission. Results. TSTEMI occurred in 20 patients (6.7%). Despite fSTR (isoelectric ST segment), occluded IRA was found in 5 of these patients (25%). Pre-PPCI TIMI flow grade 2 was found in 6 TSTEMI patients (30%). Troponin T value at 24 h after symptom onset was lower in the TSTEMI group (1.8±2.5 mg/L vs. 3.6±3.5 mg/L, P=0.008). These patients also had a lower value of brain natriuretic peptide (156.3±119.5 ng/L vs. 438.5±429.0 ng/L, P<0.001) and higher left ventricular ejection fraction (59.9±6.3% vs. 51.6±10.2%, P<0.001). All patients were followed for a median of 5.6 years during which the overall survival did not differ between the TSTEMI and STEMI groups. Conclusion. Primary PCI is strongly recommended in TSTEMI patients because of a relatively high incidence of occluded infarct related arteries. The rate of patients with TSTEMI is relatively low.